Pregnancy Outcomes Associated with Introduction of Early Diabetes Screening Guidelines - Weiss, Rebecca E.; Badreldin, Nevert; Drexler, Kathleen; Niznik, Charlotte; Yee, Lynn M. (American Journal of Perinatology, 2020)
Objective The study aimed to evaluate perinatal outcomes associated with introduction of and adherence to early diabetes screening guidelines.Study Design Retrospective cohort study of all women who received prenatal care at a single, high-volume tertiary care center before (“preguidelines”) and after (“postguidelines”) American College of Obstetrics and Gynecology guidelines for early pregnancy diabetes screening for women at high risk for diabetes. Women with known pregestational diabetes, late entry to prenatal care, a fetus with a known anomaly, or multiple gestation were excluded. Multivariable linear and logistic regression models were constructed to compare maternal and neonatal outcomes between women in the preguidelines cohort to those in the postguidelines cohort. Similarly, adherence to screening guidelines was assessed, and among all women who were eligible for early diabetes screening, multivariable linear, and logistic models were created to compare outcomes between those women who were screened early to those who were not.Results Of the 2,069 women eligible for analysis, 64.6% (n = 1,337) were in the postguideline cohort. Women in the postguideline cohort were older, less likely to have a history of smoking, and more likely to be non-Hispanic white. On multivariable analysis, women in the postguideline cohort had significantly less gestational weight gain (aβ = −2.3; 95% confidence interval [CI]: −3.4 to −1.1), but a higher odds of 5-minute Apgar's score of <7 (adjusted odds ratio: 2.51; 95% CI: 1.11–5.66). Of 461 women who met ACOG early diabetes screening criteria, 58.7% (n = 270) were screened appropriately. Adherence to screening was associated with parity, race, insurance, and BMI. On multivariable analysis, there were no significant differences in neonatal outcomes between women meeting early screening criteria who were screened early and those who were not.Conclusion Introduction of early diabetes screening guidelines was associated with a significant decrease in gestational weight gain, but did not improve neonatal outcomes.Key Points
Keywords: gestational diabetes; early screening; pregnancy outcomes; guideline adherence